"Cartas para a posteridade": tensões do modernismo brasileiro na correspondência de Mário de Andrade - Paulo Henrique Araújo (2018)
We intend to establish a link between the personal correspondence of Mário de Andrade and the power lines of his poetry, which contributed to the modernist aesthetic consecration process. We also hold a study on the rhetorical reach of the writer and the reverberations of his speech with the various correspondents. From this perspective, will be privileged discussions about the nationalist basis of the political action, the attemptto legitimize the national language and the intellectual political activism and his clash with the Christian conscience of family heirlooms, vectors that converge to the maturing of the creative process of Mario de Andrade, culminating in a self-conscious critical and sometimes pessimistic.